Pathogenesis and Mechanism of Gastrointestinal Infection With COVID-19 - Zhang, Hao; Shao, Bo; Dang, Qin; Chen, Zhuang; Zhou, Quanbo; Luo, Hong; Yuan, Weitang; Sun, Zhenqiang (Frontiers in Immunology, 2021)
As a new infectious disease, COVID-19 spreads by direct contact. Its source and pathological mechanism are not clear. The most common clinical feature is pulmonary infection. Also, a lot patients have gastrointestinal symptoms. Angiotensin converting enzyme 2 (ACE2) is a functional cellular receptor for sars-cov-2, which is like SARS-CoV, a coronavirus associated with severe acute respiratory syndrome (SARS) outbreak in the early 21st century. The tissues and cells expressing ACE2 are potential targets for sars-cov-2 infection, and the high expression of ACE2 in intestinal epithelial cells marks that sars-cov-2 may directly infect intestinal epithelial cells. Recent studies also suggest that sars-cov-2 existed and reprinted in intestinal environment for a long time. The interaction between sars-cov-2 and RAS system leads to the decrease of local anti-inflammatory ability. The virus cycle leads to excessive imbalance of immune response and cytokine release. The down-regulated of ACE2 expression after viral infection leads to gastrointestinal dysfunction. The damage of intestinal vascular endothelial cells aggravated the symptoms of toxemia. The above are the causes of gastrointestinal symptoms. We reviewed the possible causes and mechanisms of gastrointestinal symptoms caused by COVID-19. Then we discussed the influence of gastrointestinal symptoms on the prognosis of patients. And, this manuscript briefly summarized the basic of clinical treatment methods for patients with COVID-19.